PENGARUH MARKETING MIX TERHADAP LOYALITAS KONSUMEN SUPERMARKET UD. RATNA SUMBAWA BESAR - Wahyu Haryadi; S Sulistianingsih (Fakultas Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of the marketing mix on consumer loyalty at UD. Ratna Sumbawa Besar Supermarket. This type of research is associative research to determine the effect of product, price, promotion and location on consumer loyalty at UD. Ratna Sumbawa Besar Supermarket. The type of data used is quantitative data obtained from primary sources. The primary data sources in this study are consumers who have visited and made purchases at UD. Ratna Sumbawa Besar Supermarkets more than once, totaling 50 people. Data were collected through questionnaires and analyzed using multiple linear regression analysis techniques, t test (partial), f test (simultaneous) and coefficient of determination test (R2). The results showed that product, price, promotion and location had a positive and significant effect on consumer loyalty at UD. Ratna Sumbawa Besar Supermarkets, either partially or simultaneously. That is, the better the product, price, promotion and location will have an impact on increasing consumer loyalty. The effect of product, price, promotion and location on consumer loyalty at UD. Ratna Sumbawa Besar Supermarket is 87.9%, while the remaining 12.1% is influenced by other variables outside this research model, such as discounts, public relations and others.